Melting conditions in the modern Tibetan crust since the Miocene - Jinyu Chen (Nature Portfolio, 2018)
Crustal melting may play a fundamental role in orogenic processes, but quantifying crustal melt remains difficult. Here, the authors combine pressure-temperature paths, electrical conductivity and geophysical data to elucidate the melting conditions in Tibet since the Miocene.